Effect of drink temperature on core temperature and endurance cycling performance in warm, humid conditions - Burdon, C.; O'Connor, H.; Gifford, J.; Shirreffs, S.; Chapman, P.; Johnson, N. (Journal of Sports Sciences, 2010)
The aims of this study were to determine the effect of cold (4°C) and thermoneutral (37°C) beverages on thermoregulation and performance in the heat and to explore sensory factors associated with ingesting a cold stimulus. Seven males (age 32.8 ± 6.1 years, VO2peak 59.4 ± 6.6 ml/kg·min) completed cold, thermoneutral, and thermoneutral + ice trials in randomized order. Participants cycled for 90 min at 65%VO2peak followed by a 15-min performance test at 28°C and 70% relative humidity. They ingested 2.3 ml/kg of a 7.4% carbohydrate-electrolyte solution every 10 min during the 90-min steady-state exercise including 30 ml ice puree every 5 min in the ice trial. Absolute changes in skin temperature (0.22 ± 1.1°C vs. 1.14 ± 0.9°C; P = 0.02), mean body temperature (1.2 ± 0.3 vs. 1.6 ± 0.3°C; P = 0.03), and heat storage were lower across the 90-min exercise bout for the cold compared with the thermoneutral trial. Significant improvements (4.9 ± 2.4%, P < 0.01) in performance were observed with cold but no significant differences were detected with ice. Consumption of cold beverages during prolonged exercise in the heat improves body temperature measures and performance. Consumption of ice did not reveal a sensory response, but requires further study. Beverages consumed by athletes exercising in the heat should perhaps be cold for performance and safety reasons.